CameraIcon
CameraIcon
SearchIcon
MyQuestionIcon


Question

For solving each pair of equations, use the method of eliminations by equating coefficients:

13+2y=9x

3y=7x


Solution

13+2y=9x
9x-2y=13------------eq.1
3y=7x
7x-3y=0-----------eq.2

Solving both the equation,

Eq. 1 ×  3 ➡27x - 6y=39
Eq. 2 × 2 ➡14x - 6y =0
----------------------
13x = 39
x=3

Substituting the value of x in equation 2,

7x-3y=0
7× 3-3y=0
-3y=-21
y=7


Mathematics
Concise Mathematics
Standard IX

Suggest Corrections
thumbs-up
 
0


similar_icon
Similar questions
View More


similar_icon
Same exercise questions
View More


similar_icon
People also searched for
View More



footer-image